Perceptions of risk factors associated with coronary disease (Research, Society and Development, 2022)
This study aimed to analyze the perception of patients and the prevalence of systemic and oral risk factors in patients with coronary artery disease (CAD). This is a quali-quantitative study in which 56 patients with CAD had quantitative and qualitative data collected and analyzed. Of the 56 patients who made up the sample, 41 had their oral cavity examined and 11 were interviewed. Of this total, 46.42% have no education; 64.28% are unemployed; 72.41% have low family income; 25% are smokers; 17.85 are obese; 76.78% have hypertension; 30.36% diabetes; and 64.29% admitted having inadequate eating habits. In the qualitative analysis, 4 (four) categories emerged from the interviews and it was possible to identify, in general, the lack of knowledge of risk factors regardless of education level. In general, it was observed that, in this study, the social and demographic conditions and morbidity rates of the studied population were worse than the average of data from regional and national registries. The perception of risk factors as a cause of CAD was low and regardless of education level. The population studied showed a higher prevalence of risk factors when compared to regional and national averages. These facts may have increased the subjects' vulnerability and contributed to the development of CAD.